Contrasting thermal behaviors in Σ3 grain boundary motion in nickel. (15th August 2019) - Humberson, Jonathan; Chesser, Ian; Holm, Elizabeth A.
Abstract: Synthetic driving force molecular dynamics simulations were utilized to survey grain boundary mobility in three classes of incoherent Σ3 twin boundaries: <112>, <110>, and <111> tilt boundaries. These boundaries are faceted on low energy planes, and step flow boundary motion occurs by glide of the triplets of partial dislocations that comprise the mobile facets. Systematic trends with inclination angle are identified and characterized. Observations of thermally activated, anti-thermal, and athermal motion are explained in terms of the orientation of the Shockley partial dislocations along close-packed and non-close-packed directions. Thermally activated <112> tilt boundaries with 110 twin facets are found to have smaller energy barriers to motion than <110> tilt boundaries with 112 twin facets. Thermally activated boundaries follow a compensation effect associated with a facet roughening transition. As for all faceting boundaries, system size and driving force must be chosen with care to prevent simulation artifacts. Graphical abstract: Image 1